Sensory Integrative Processing in Delinquent-Prone and Non-Delinquent-Prone Adolescents. - Shan-Pin Fanchiang; Snyder, Carolyn; Zobel-Lachiusa, Jeanne; Loeffler, Carol Bartolo; Thompson, Mary Ellen (American Journal of Occupational Therapy, 1990)
The purposes of this study were to obtain a preliminary description of the sensory integrative and practic abilities of 114 non-delinquent-prone adolescents aged 12 through 18 years and to compare their performances with those of 12 delinquent-prone adolescents with learning problems. Ten of the 17 subtests of the Sensory Integration and Praxis Tests (SIPT) (Ayres, 1989) as well as the Finger Posture Imitation Test (Druker, 1980) and the MacQuarrie Test for Mechanical Ability (MacQuarrie, 1925/1953) were administered to both groups. It was hypothesized that performance on some tests would correlate with age in the non-delinquent-prone adolescents. It was also hypothesized that some delinquent-prone adolescents with learning problems would perform significantly worse on the tests of sensory integrative and practic abilities than would the non-delinquent-prone adolescents. A data analysis indicated that performance on the praxis tests, Manual Form Perception, Graphesthesia, and Bilateral Motor Coordination showed a significant age correlation. The results of this study indicated a difference between the two groups, and it was concluded that the delinquent-prone group performed more poorly on all of the praxis-related tests and on the absolute values of the tests of Postrotary Nystagmus, Standing and Walking Balance, and Bilateral Motor Coordination. Some of the vestibular- and praxis-related tests, therefore, may still provide useful information on children older than 8 years of age.